Exploring the Power of Qur'anic Parenting to Build Family Resilience - Harahap, Aziddin; Harahap, Arman; Febriani, Budi; Pardamean, Muda; Syahputra Harahap, Hasmi (International Journal of Educational Research & Social Sciences, 2025)
Parenting is the maximum effort of parents given to children to become individuals with noble character. Parenting patterns or parenting in Islam, is a complete unity that comes from the attitude of parents towards young children in how to care for, educate, guide, and foster children optimally based on the Qur'an and the Sunnah of the Prophet. The role of parents as a foundation in the household greatly influences the growth and development of children's attitudes, because the beginning of a child's life is in the hands of parents, this is as the Prophet said "Every child is born in a state of fitrah, then both parents make him a Jew, a Christian, or a Magian" (HR. Bukhori). In addition, parents also have many advantages in educating children, such as being able to care for children all the time with love, and being able to pay attention to each of their developments. This is different from education in schools which only takes half a day and is structured.In Q.S An-Nisa: 9. Talk to them (children) gently, kindly, politely, and call them with pleasant nicknames, such as my son, my darling, etc. Meanwhile, in Q.S An-Nisa: 9 with the word falyattaqullah, which means "Be fearful of Allah" has the intention of being able to equip children with aqeedah. So based on the last verse in Q.S An-Nisa: 9 which reads wal yaquuluu qaulan sadiida, which means "and let them say the correct sentences". Based on the last paragraph, the responsibility of parents in educating children is to have good morals and say the right words.